DIGITAL TRANSFORMATION OF ONLINE LEARNING TOOLS ADOPTED BY HIGHER EDUCATION INSTITUTIONS IN HARYANA DURING THE PANDEMIC (IITM Journal of Business Studies, 2024)
The COVID-19 pandemic has precipitated  unprecedented changes across various  sectors, with education being one of the most  significantly impacted. As higher education  institutions swiftly transitioned from traditional  in-person teaching methods to online platforms,  the need to assess and understand this digital  transformation has become critical. This  research paper explores the adoption of online  learning tools by higher education institutions  in Haryana during the pandemic, employing a  qualitative research methodology to gain deeper  insights into the experiences, challenges, and  outcomes associated with this shift. Utilizing a self-administered questionnaire,  the study captures the perspectives of 200  teachers from higher education institutions  across Haryana. The questionnaire is designed  to probe various facets of the digital transition,  including the selection of tools, the effectiveness  of online teaching methodologies, the challenges  faced by educators in engaging students, and  the overall impact on the educational process.  Responses will be analyzed to identify patterns  and themes that shed light on the effectiveness  of the digital tools and strategies implemented  during the pandemic.
Keywords: Digital Transformation Learning Tools in Higher Education Institutions (HEIs) in Haryana.